Perancangan Sistem Pembangkit Listrik Hibrida untuk Menggerakkan Pompa Air di Area Pertanian - Fazri Fazri; Ahmad Syuhada; Zahrul Fuadi (Jurnal Teknik Mesin Unsyiah, 2016)
The economic development and population growth in Indonesia has been increasing rapidly. Most of the agricultural land converted into residential and industrial areas, while many farmers moved to a mountainous area. Farmers in mountainous agricultural area using existing sources of water in a small mountainous rivers to irrigate agricultural land, they use man power to lift water from a small river to agricultural land, it is highly ineffective in agricultural products. Farmers with adequate financial can use pumps for raising the water to agricultural land. But because it is far from the power source, pump can only work with the use of expensive fossil fuels. Therefore, to overcome this problem it is necessary to use a renewable energy source which is available in the area such as solar energy and wind or both of them. This research examines about the hybrid power plant (PLTH) of solar and wind energy to power the agriculture pump. The wind speed and solar radiation data is obtained from measurements by BMKG-SMPK-Plus Sare. The output power of the Photovoltaic is equal to 193 W with the exposure time of 5 hours/day, while the power output of the wind turbine is 459.84 W with a 3m blade diameter long and 7 hours/day blowing wind. The pump power was 558 W with a capacity of 20,160 liters/hour, it is used for 15 ha of agricultural area. Based on the analysis results, the proposed system will generate an initial investment cost of US 14.938 with power production equal to 3.210 kW/year.